2020
DOI: 10.1177/1532673x20975329
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Ideological Asymmetry in Public Attitudes Toward Political Protest

Abstract: Political protests cannot succeed without public support. Extant studies point to weaker average support among ideological conservatives, but researchers have yet to consider the extent to which such apparent ideological asymmetry is (a) an artifact of the particular protest cases that researchers have tended to investigate, and/or (b) conditioned by the precise meaning of “ideological conservatism.” In this investigation, we address these gaps. Specifically, we analyze public perceptions of protest legitimacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…“(R)” indicates that, for ease of use, in S7 the original measure of negative beliefs about equal opportunity was reversed to reflect perceptions of social inequality. S1: Arora and Stout 2019; S2: Barker, Nalder, and Newham 2021; S3: Bonilla and Tillery 2020; S4: Cole 2020; S5: Corral 2020; S6: Drakulich et al 2020; S7: Holt 2018; S8: Holt and Sweitzer 2018; S9: Hordge-Freeman and Loblack 2020; S10: Ilchi and Frank 2020; S11: Lake, Alston, and Kahn 2018; S12: Meleady and Vermue 2019; S13: Merseth 2018; S14: Riley and Peterson 2020; S15: Seaton et al 2020; S16: Selvanathan, Lickel, and Jetten 2020; S17: Selvanathan et al 2018; S18: Towler, Crawford, and Bennett 2020; S19: Updegrove et al 2020; S20: Watson-Singleton et al 2020; S21: Wouters 2019. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…“(R)” indicates that, for ease of use, in S7 the original measure of negative beliefs about equal opportunity was reversed to reflect perceptions of social inequality. S1: Arora and Stout 2019; S2: Barker, Nalder, and Newham 2021; S3: Bonilla and Tillery 2020; S4: Cole 2020; S5: Corral 2020; S6: Drakulich et al 2020; S7: Holt 2018; S8: Holt and Sweitzer 2018; S9: Hordge-Freeman and Loblack 2020; S10: Ilchi and Frank 2020; S11: Lake, Alston, and Kahn 2018; S12: Meleady and Vermue 2019; S13: Merseth 2018; S14: Riley and Peterson 2020; S15: Seaton et al 2020; S16: Selvanathan, Lickel, and Jetten 2020; S17: Selvanathan et al 2018; S18: Towler, Crawford, and Bennett 2020; S19: Updegrove et al 2020; S20: Watson-Singleton et al 2020; S21: Wouters 2019. …”
Section: Resultsmentioning
confidence: 99%
“…Published studies have found a range of factors contributing to participation in BLM protests including intergroup contact (Meleady and Vermue 2019), empathy-mediated contact (Selvanathan et al 2018), and perceived societal inequality (Lake, Alston, and Kahn 2018). Support for BLM has been linked to identifying as Democrats (Arora and Stout 2019), endorsement of progressive-liberal politics (Merseth 2018), recognizing society lacks equal opportunities (Holt 2018), as well as to psychological tendencies such as lower levels of both authoritarianism (Barker, Nalder, and Newham 2021), and social dominance orientation (Holt and Sweitzer 2018). Additionally, Sawyer and Gampa (2018) found that during BLM protests, liberals tend to display less pro-white implicit and explicit bias than conservatives.…”
Section: State Of the Artmentioning
confidence: 99%
“…It, therefore, includes unauthorized forms of unconventional participation; acts of civil disobedience; seizing of public or private buildings; participating in confrontations with different the police or other civil groups; and other acts of political violence against private or public property or against people (Finkel et al, 1989). What defines these types of acts is that they defy established authority (Barker et al, 2021) and violate existing laws and existing social norms (Wright & Citrin, 2011). Hence, to uncover who is more likely to be engaged in spiral processes of illegal protest and violence escalation, we suggest focusing on the political values that are specifically related to law, order, and authority, which are the principles related to the core definition of illegal protest itself.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to this scholarship, authoritarianism praises obedience, social order, and deference to authorities perceived as legitimate (Glas & Taylor, 2018). The key concept here is legitimacy since some authoritarians defending cultural and social order might well justify disruptive or even undemocratic means (Barker et al, 2021). In an era of multi-issue activism (Andersen & Jennings, 2010), those issues framed as cultural threats to national or society unity (Wright & Citrin, 2011) might activate some authoritarian people into illegal protest networks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation